GC/MS analysis and potential synergistic effect of mandarin and marjoram oils on Helicobacter pylori - Rawah H. Elkousy; Nada M. Mostafa; Ahmed M. Abd-alkhalek; Mahmoud A. El Hassab; Sara T. Al-Rashood; Wagdy M. Eldehna; Omayma A. Eldahshan (Taylor & Francis Group, 2022)
Helicobacter pylori can cause chronic gastritis, peptic ulcer, and gastric carcinoma. This study compares chemical composition and anti-H. pylori activity of mandarin leaves and marjoram herb essential oils, and their combined oil. GC/MS analysis of mandarin oil revealed six compounds (100% identified), mainly methyl-N-methyl anthranilate (89.93%), and 13 compounds (93.52% identified) of marjoram oil, mainly trans-sabinene hydrate (36.11%), terpinen-4-ol (17.97%), linalyl acetate (9.18%), and caryophyllene oxide (8.25%)). Marjoram oil (MIC = 11.40 µg/mL) demonstrated higher activity than mandarin oil (MIC = 31.25 µg/mL). The combined oil showed a synergistic effect at MIC of 1.95 µg/mL (same as clarithromycin). In-silico molecular docking on H. pylori urease, CagA, pharmacokinetic and toxicity studies were performed on major compounds from both oils. The best scores were for caryophyllene oxide then linalyl acetate and methyl-N-methyl anthranilate. Compounds revealed high safety and desirable properties. The combined oil can be an excellent candidate to manage H. pylori.